Stearoyl Lysophosphatidylcholine Inhibits Endotoxin-Induced Caspase-11 Activation. Issue 3 (September 2018) - Li, Wenbo; Zhang, Wei; Deng, Meihong; Loughran, Patricia; Tang, Yiting; Liao, Hong; Zhang, Xianying; Liu, Jian; Billiar, Timothy R.; Lu, Ben
Abstract : ABSTRACT: Stearoyl lysophosphatidylcholine (LPC) exerts protective effect during endotoxemia and in experimental sepsis, but the underlying mechanism is unclear. Here, we demonstrated that stearoyl LPC could block caspase-11-mediated macrophage pyroptosis. In vitro, stearoyl LPC significantly decreased caspase-11 activation and pyroptosis induced by lipopolysaccharide (LPS) plus cholera toxin subunit B independent of the receptor G2A. Stearoyl LPC did not affect LPS uptake by mouse peritoneal macrophages but did significantly inhibit the interaction between LPS and caspase-11. Moreover, stearoyl LPC treatment conferred significant protection against lethal endotoxemia and significantly reduced the release of IL-1α and IL-1β. These findings identify stearoyl LPC as an inhibitor of LPS-mediated caspase-11 activation. This mechanism could explain the protective action of stearoyl LPC in experimental sepsis and endotoxemia.